Preparation of high quality ferrovanadium nitride by carbothermal reduction nitridation process - Zhang, Guo-Hua; Wu, Yue-Dong; Chou, Kuo-Chih (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
In this paper, high quality ferrovanadium nitride was prepared successfully under nitrogen atmosphere above 1573 K, by using the reactants of V2O5, Fe and C. The effect of reaction temperature, C/O molar ratio and sampling method on the prepared ferrovanadium nitride were investigated in details. It was demonstrated that C/O molar ratio (content of O is defined as the oxygen in V2O5) had a great influence on the residue carbon, as well as the nitrogen content in the final products. It was found that the nitrogen content of the prepared ferrovanadium nitride first increased and then decreased with the increase of C/O molar ratio, with the optimum C/O molar ratio to be 90% of the stoichiometric value. When the temperature was higher than 1773 K, Fe became liquid phase and surrounded the solid V(C, N, O) particles tightly. The formation of liquid Fe was beneficial to the further removal of oxygen atoms remained in the lattice of V(C, N, O), since it provided a liquid tunnel for carbon diffusion which greatly enhanced the reaction kinetics. From the results of X-ray diffraction (XRD) and thermodynamic calculation, phase evolution sequence can be obtained: V2O5→VO2→V2O3→V(C, N, O). Moreover, the kinetic process from V2O3 to VN was studied and the results shown that the reaction rate can be described by Jander diffusion model with the extracted activation energy of 188.173 kJ/mol.